Gastric Mucormycosis Masquerading as Malignancy: A Rare and Fatal Disease - Tiwari, Shreshtha; Parakh, Deepshikha; Ojha, Sandeep; Lade, Gaurav; Jain, Nikhil; Biswas, Dipanjan (Annals of Pathology and Laboratory Medicine, 2025)
Gastric mucormycosis is a rare, life-threatening fungal infection that often presents with nonspecific gastrointestinal symptoms, making its diagnosis challenging. We report a case of a 59-year-old postmenopausal female with a history of Gudakhu use, who presented with persistent vomiting for six months. Imaging and endoscopy initially suggested a gastric malignancy. However, histopathological examination confirmed gastric mucormycosis. This case highlights the importance of considering fungal infections in the differential diagnosis of gastric masses, especially in endemic areas.